2021
DOI: 10.1002/jum.15694
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Erector Spinae Plane Block and Trapezius Muscle Injection for Myofascial Pain Syndrome

Abstract: Objective There were two goals to this study: the first goal was to research the analgesic effectiveness of erector spinae plane block (ESPB) added to the treatment after trapezius muscle injection (TMI) and the second was to investigate whether repeated TMI increases the analgesic effect in myofascial pain syndrome (MPS). Methods Sixty patients with a diagnosis of MPS were randomized into two groups. The TMI group (n = 30) received ultrasound‐guided (USG) TMI with 5 mL of 0.25% bupivacaine two times, with a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Ultrasound-guided nerve blocks have been shown to be efficacious for the treatment of musculoskeletal pain and neuropathic pain. 12 , 13 With the progressive integration of ultrasound in emergency medicine practice, ultrasound-guided nerve blockade for procedural analgesia, fracture analgesia, and atraumatic conditions such as sciatica, has become more commonplace. 14 , 15 The LFCN is a superficial, purely sensory nerve that is amenable to visualization on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided nerve blocks have been shown to be efficacious for the treatment of musculoskeletal pain and neuropathic pain. 12 , 13 With the progressive integration of ultrasound in emergency medicine practice, ultrasound-guided nerve blockade for procedural analgesia, fracture analgesia, and atraumatic conditions such as sciatica, has become more commonplace. 14 , 15 The LFCN is a superficial, purely sensory nerve that is amenable to visualization on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ESP blocks in chronic myofascial pain (cervical and interscapular) was first reported in 2019, and randomized studies have shown that the ESP block is an effective pain relief method both when added to traditional treatment and when used alone [ 60 , 61 ]. However, as the source of pain in myofascial pain syndromes is controversial, the mechanism of this pain relief of ESP blocks and similar fascial plane blocks has not been fully clarified.…”
Section: Esp Block and Chronic Painmentioning
confidence: 99%
“…Since being first defined, erector spinae plane block (ESPB) has been described as being “safer” by various authors, owing to its distance from neural and vascular tissues and its relatively low reported complication rates 1,2 . Although a PubMed search reveals over 900 papers on ESPB as of March 2022, these papers report very few complications.…”
Section: Figurementioning
confidence: 99%
“…
ince being first defined, erector spinae plane block (ESPB) has been described as being "safer" by various authors, owing to its distance from neural and vascular tissues and its relatively low reported complication rates. 1,2 Although a PubMed search reveals over 900 papers on ESPB as of March 2022, these papers report very few complications. All complications of ESPB such as motor block, the spread of local anesthetic (LA) to the opposite side, priapism, and Harlequin syndrome are related to the spread of LA to the paravertebral space and the sympathetic chain.
…”
mentioning
confidence: 99%